AUDIOBOOKS AS MEDIA TO INCREASE LISTENING AND SPEAKING SKILLS: A QUALITATIVE SYSTEMATIC REVIEW - Rizal, Daviq; Masruroh, Siti; Rahman Syah, Raikhan Fatkur; Fathina, Ika Fatra; Amrullah, M. Furqan; Zakariyah, Saiful (ETERNAL (English, Teaching, Learning, and Research Journal), 2022)
Numerous studies have been conducted on the usage of audiobooks. However, a qualitative systematic evaluation of the use of audiobooks for the development of listening and speaking abilities has not yet been done. The purpose of this research was to conduct a review of journal publications on the use of audiobooks to improve listening and speaking abilities. By using a qualitative systematic review, the researchers conducted a search of Google Scholar for 390 reference materials on audiobooks as media for teaching listening and speaking. Only three articles were collected and included in the analysis by using coding and classification. The results showed that audiobooks assist students in strengthening their listening and speaking skills. An audiobook cannot replace a teacher and should be utilized in conjunction with other educational materials. Further researchers could conduct research on the audiobooks of non-native English speakers in educational materials.